Zinc finger protein ZC3H18 is abnormally expressed in esophageal cancer tissues and facilitates the proliferation of esophageal cancer cells - Zhang, Yujin; Wan, Yilong; Li, Jiaxi; Ju, Sheng; Tong, Xin; Wu, Ji; Wu, Hao; Zhang, Liuqing; Shao, Shengxiang; Wang, Yuhong; Guo, Lingchuan; Zhao, Jun; et al. (Frontiers in Immunology, 2025)
IntroductionEsophageal cancer presents significant challenges due to the limited efficacy and severe side effects associated with conventional treatments. The identification of epigenetic regulatory molecules that are aberrantly expressed in tumors is crucial for elucidating the mechanisms underlying the development and progression of esophageal cancer.MethodsWe performed high-throughput methylation level analysis on cancerous and adjacent tissues from 25 patients, identifying the differentially methylated gene ZC3H18 utilizing Bismark software and data from TCGA. Esophageal cancer cell lines with ZC3H18 knockdown were used to validate the biological role of ZC3H18 in tumorigenesis in vitro and in vivo. Eukaryotic transcriptome sequencing analysis was conducted to investigate the potential mechanisms underlying ZC3H18 function.ResultsWe identified 30 genes exhibiting significant methylation differences between cancerous and adjacent non-cancerous tissues in 25 patients. Subsequent analysis utilizing the TCGA database revealed that the gene ZC3H18 is aberrantly expressed in tumor tissues and is closely associated with patient prognosis. Examination of esophageal cancer tissue samples demonstrated overexpression of the ZC3H18 protein, which was positively correlated with adverse prognosis indicators, including tumor differentiation, stage, and invasion depth. ZC3H18 knockdown significantly inhibited cellular proliferation, migration, invasion, and damage repair. Additionally, ZC3H18 significantly promoted tumor growth in vivo. The expression of various cytokeratins was significantly reduced following the ZC3H18 gene knockdown. ZC3H18 and multiple keratins were co-localized in esophageal cancer tissue.DiscussionZC3H18 gene exhibits differential methylation in esophageal cancer was positively correlated with unfavorable patient prognosis. ZC3H18 plays a critical role in the regulation of biological functions within esophageal tumors.